Absorption of Sulfur Dioxide by Tetraglyme–Sodium Salt Ionic Liquid - Qiang Xu; Wei Jiang; Jianbai Xiao; Xionghui Wei (Molecules, 2019)
A series of tetraglyme⁻sodium salt ionic liquids have been prepared and found to be promising solvents to absorb SO2. The experiments here show that [Na⁻tetraglyme][SCN] ionic liquid has excellent thermal stability and a 30% increase in SO2 absorption capacity compared to other sodium salt ionic liquids and the previously studied lithium salt ionic liquids in terms of molar absorption capacity. The interaction between SO2 and the ionic liquid was concluded to be physical absorption by IR and NMR.